Analisis Penerapan E-Accounting Untuk Meningkatkan Tata Kelola Dan Mencegah Kecurangan Pada Penyusunan Laporan Keuangan Pemerintah Daerah : Studi Pada BPKAD Kota Surabaya - Atakelan, Reinatto Yakobus Pati Agon; Muhammad Taufiq Hidayat (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the implementation of e-Accounting in improving governance and preventing conditions in the preparation of Regional Government Financial Reports (LKPD) at the BPKAD of Surabaya City. The study used a qualitative descriptive approach through in-depth interviews, observation, and documentation, with informants from the Head of the Accounting Team and the BPKAD accounting supervisor. The results of the study indicate that the implementation of e-Accounting is effective and has a significant impact in four main aspects. First, the system is able to increase the effectiveness of the LKPD preparation process through automatic data retrieval, system validation, and cross-unit integration, thereby minimizing manual errors. Second, e-Accounting strengthens governance through transparency, accountability, and access rights retrieval. Third, the system has been proven to provide opportunities for fraud. Fourth, e-Accounting improves the quality of financial reports because the data produced is faster, more accurate, and in accordance with accrual-based SAP standards